Policing and public trust: exposing the inner uniform - De Jonge, Eccy (The applied criminology across the globe series, 2021)
"Victims and complainants are routinely discredited by policing agencies around the globe. Examining stories of people who have been targeted by police, Dr. Eccy de Jonge reveals how the inner workings of this public institution are failing those who rely upon it the most"--